A Dispensable Chromosome Is Required for Virulence in the Hemibiotrophic Plant Pathogen Colletotrichum higginsianum - Plaumann, Peter-Louis; Schmidpeter, Johannes; Dahl, Marlis; Taher, Leila; Koch, Christian (Frontiers in Microbiology, 2018)
The hemibiotrophic plant pathogen Colletotrichum higginsianum infects Brassicaceae and in combination with Arabidopsis thaliana, represents an important model system to investigate various ecologically important fungal pathogens and their infection strategies. After penetration of plant cells by appressoria, C. higginsianum establishes large biotrophic primary hyphae in the first infected cell. Shortly thereafter, a switch to necrotrophic growth occurs leading to the invasion of neighboring cells by secondary hyphae. In a forward genetic screen for virulence mutants by insertional mutagenesis, we identified mutants that penetrate the plant but show a defect in the passage from biotrophy to necrotrophy. Genome sequencing and pulsed-field gel electrophoresis revealed that two mutants were lacking chromosome 11, encoding potential pathogenicity genes. We established a chromosome loss assay to verify that strains lacking this small chromosome abort infection during biotrophy, while their ability to grow on artificial media was not affected. C. higginsianum harbours a second small chromosome, which can be lost without effect on virulence or growth on agar plates. Furthermore, we found that chromosome 11 is required to suppress Arabidopsis thaliana plant defense mechanisms dependent on tryptophan derived secondary metabolites.